Association Between Needle Sharing Behavior and HIV/HCV Coinfection Incidents in Injecting Drug Users - Nurul Dwi Mukti; Putri Permatasari; Apriningsih Apriningsih; Terry Yuliana Rahadian Pristya (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
The 2018-2019 Integrated Biological and Behavioral Survey (IBBS) reported that Human Immunodeficiency Virus/Hepatitis C Virus (HIV/HCV) coinfection was most prevalent among Injecting Drug Users (IDUs), reaching 69.7%. Needle sharing behavior among IDUs can increase the risk of exposure to bloodborne infection such as HIV and HCV. This study aimed to examine the association between needle sharing behavior and HIV/HCV coinfection among IDUs in West Java Province, using data from 2018-2019 IBBS and a cross-sectional study design. Respondent-Driven Sampling technique was employed in the 2018-2019 IBBS, yielding 1,478 samples. Data analysis was conducted up to the multivariate stage using Cox regression. The prevalence of HIV/HCV coinfection among IDUs in West Java was found to be 6.8%. Needle sharing behavior was not significantly associated with HIV/HCV coinfection among IDUs (APR: 0.77; 95% CI: 0.41–1.45; p-value = 0.424), with confounding variables being gender, history of incarceration, and duration of injecting drug use, where the most significant variable was a history of incarceration (APR: 3.29; 95% CI: 2.19–4.93; p-value < 0.001). Health interventions should prioritize IDUs with a history of incarceration. Strengthening health services and harm reduction programs in correctional facilities, providing education on HIV/HCV prevention, and developing reintegration programs for formerly incarcerated IDUs are necessary.